2010
DOI: 10.1038/ajg.2009.747
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features of Pancreatic Endocrine Tumors: A Prospective Multicenter Study in Italy of 297 Sporadic Cases

Abstract: This study points out the high number of new cases of PETs observed in Italy, with a high prevalence of NF and incidentally discovered forms. The size of the tumor was smaller and the rate of metastasis was lower than usually reported, suggesting a trend toward an earlier diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(76 citation statements)
references
References 48 publications
3
69
1
3
Order By: Relevance
“…Less common are internal haemorrhages (4-20%), jaundice (17-50%) or palpable tumours in the abdomen (7-40%) [2,[24][25][26]. Recent studies by Italian researchers have demonstrated that hepatic metastases are observed in 32% of patients with a newly diagnosed NF-PNEN [27]. This value is significantly lower compared to previous studies (46-73%) [21,[28][29][30].…”
Section: Clinical Characteristics Of Pnencontrasting
confidence: 50%
“…Less common are internal haemorrhages (4-20%), jaundice (17-50%) or palpable tumours in the abdomen (7-40%) [2,[24][25][26]. Recent studies by Italian researchers have demonstrated that hepatic metastases are observed in 32% of patients with a newly diagnosed NF-PNEN [27]. This value is significantly lower compared to previous studies (46-73%) [21,[28][29][30].…”
Section: Clinical Characteristics Of Pnencontrasting
confidence: 50%
“…In rare cases, in both familiar and more rarely sporadic NFNENs, the tumor may become functional during the clinical course and present hormonal symptoms. A recent Italian multicenter observational study [15] showed that 32% of NF pancreatic NETs present liver metastases at first diagnosis although this rate is slightly lower than those currently reported in the literature where rates ranging from 46 to 73% are described [3,5,[16][17][18][19][20][21][22][23] . According to SEER data [3] , localized, regional, and distant stages corresponded to 14,23, and 54% of cases.…”
Section: Clinical Presentationmentioning
confidence: 58%
“…Most authors, however, have made this distinction [5,6,7,9,[22][23][24][25][26][27][28][29][30][31] and have agreed that histological differentiation has significant effect on prognosis. Eight of these authors have presented incidence data of poorly differentiated carcinomas (8-21%) [5,6,7,9,17,27,28,31].…”
Section: Discussionmentioning
confidence: 99%